Whole genome sequencing of the Canine Distemper Virus isolated from dog in 2018 - Thi Roan, Do; Duc Thanh, Do; Thi Mai Lan, Dang; Hong Ngoc, Pham; Huu Duc, Nguyen; Thi Khue, Nguyen; Thi Thu Hien, Nguyen; Kim Xuyen, Le Thi; Thanh Hoa, Le; Thi Thanh Huong, Doan (Vietnam Journal of Biotechnology, 2020)
The complete nucleotide genome sequence for Canine Distemper Virus strain CDVHN5 isolated from a dog in Hanoi, Vietnam, in 2018, was determined and phylogenetically analyzed. The complete genome size of the CDVHN5 strain was 15,690 nucleotides, encoding for 02 non-structural proteins (C and V protein) and 06 structural proteins (large protein (L), haemagglutinin (H), phosphoprotein (P), nucleocapsid protein (N), fusion protein (F) và matrix protein (M). In the genome, base A accounted for the highest percentage of 30.5%, consisted of 4,798 nucleotides. Base T consisted of 4,177 nucleotides, accounted for 26.62%. Base G consisted of 3,450 nucleotides, accounted for 21.7%. And base C consisted of 3,310 nucleotides, accounted for 21.1%. The percentage of A+T was 57.2%, higher than that of G+C (42.8%). Nucleotide sequencing analysis showed that the CDVHN5 strain had the highest similarity (99.7%) compared with the virulent strain collected in Ho Chi Minh City in 2014 (CDV/dog/HCM/33/140816) that belongs to genotype Asia-1. Comparison to other genotypes, the CDVHN5 strain had a low percentage of nucleotide and amino acid similarities, from 92.4% to 96%, among them, the lowest rate with two strains of vaccine virus Onderstepoort-US-2002 belonging to genotype America-1 and CDV2784-IT-2013 strain of genotype Arctic (92.4%). Phylogenetic analysis showed that the CDVHN5 strain in Hanoi belonged to genotype Asia-1, similar to Chinese, Taiwan, Thailand and Korean strains. To date, the only full-length CDV sequence from Ho Chi Minh City was sequenced and published in Genebank, no data from Northern Vietnam. So that, the addition of whole genome sequence of CDV in Vietnam is essential.